2017
DOI: 10.3897/compcytogen.v11i2.11980
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on Boreonectes Angus, 2010, with a molecular phylogeny of the Palaearctic species of the genus

Abstract: Karyotypes are given for Boreonectes emmerichi (Falkenström, 1936) from its type locality at Kangding, China, and for B. alpestris (Dutton & Angus, 2007) from the St Gotthard and San Bernardino passes in the Swiss Alps. A phylogeny based on sequence data from a combination of mitochondrial and nuclear genes recovered western Palaearctic species of Boreonectes as monophyletic with strong support. Boreonectes emmerichi was placed as sister to the north American forms of B. griseostriatus (De Geer, 1774), althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… multilineatus are given by Foster et al (2016) . The only other records for this species are from the Faroe Islands, the material in this case being identified by DNA analysis ( Angus et al 2017 ). Irish B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… multilineatus are given by Foster et al (2016) . The only other records for this species are from the Faroe Islands, the material in this case being identified by DNA analysis ( Angus et al 2017 ). Irish B.…”
Section: Resultsmentioning
confidence: 99%
“… alpestris e paratype ♂, Italy, Dolomites, Falcade, shown as fig. 2f by Dutton and Angus (2007) f, g ♂, Italy, Gran Paradiso, Colle del Nivolet e plain f C-banded, shown as fig.1b, c by Angus et al (2017) h, i ♀, Switzerland, Ticino, San Bernardino pass h plain i C-banded, shown as fig. 1d, e by Angus et al (2017) j paratype ♀, Switzerland, Ticino, Medeglia, plain, shown as fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations